PTU-252 Higher emergency laparotomy mortality rates in over 65s with higher p-possum scores. (22nd June 2015) - Brown, S; Ray, C; Edwards, J; French, N; Moug, S
Abstract : Introduction: Various factors are associated with increased laparotomy mortality rates, the study of which could help with the difficult decision of which patients should not have laparotomy as they are unlikely to survive. P-POSSUM in some studies has been shown to predict laparotomy survival and we were keen to assess if this persists in different age groups. Method: A prospective database had been created of 144 consecutive laparotomy patients in a busy district general hospital, using locally tabulated and National Laparotomy Database data, to allow calculation of 30-day mortality, and analysis of various patient factors. A previous multivariate analysis, performed using Cox Proportional Hazards Analysis, had suggested that age and postoperative P-POSSUM were independent predictors of mortality. For this study, mortality rates were calculated for patients over 65, and over 80, and separately within each category for those whose P-POSSUM scores were under and equal to or over the mean values, with the differences being assessed with chi-squared analysis. Results: Mean age of the patients was 63.3 (13–92). Overall mean P-POSSUM score was 17.2%. 50% of the patients were over 65 and 25% over 80. In the patients who were over 65, mortality was 29%. In those over-65s who had a P-POSSUM score equal to or over the mean, mortality was 44.8% and in those under the mean it was 17% (p = 0.014). In patients over 80, mortality was 36%. In octogenarians who had a P-POSSUM score equal to or over the mean, mortality was 40% and in those under, 33.3% and this was not a significant difference (p = 0.734). Conclusion: In the over-65s POSSUM scoring signficiantly divides this population into higher and lower mortality, which could be used to direct operative decisions. In the over 80s this difference cannot be shown, potentially due to being over 80 itself being such a strong predictor of laparotomy mortality. Disclosure of interest: None Declared.